Preparation method of glucose response type genetic material delivery hydrogel
By using glucose-responsive genetic material to deliver hydrogels on diabetic wounds, loading GOx, MnO2 and miR-146a, the problem of difficulty in healing in diabetic wounds is solved, local blood glucose regulation and microenvironment stability are achieved, and wound healing is promoted.
Patent Information
- Application Number
- CN202510109971.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The difficulty in healing of diabetic wounds mainly stems from inflammatory responses caused by high sugar environments, elevated reactive oxygen levels, local hypoxia and imbalance in macrophage polarization. The existing treatment methods have problems such as limited anti-inflammatory effects, insufficient antioxidant efficiency and lack of intelligent response.
The hydrogel is delivered by glucose-responsive genetic material. By introducing borate ester bonds into the hydrogel, GOx, MnO2 and miR-146a are loaded, and GOx is used to catalyze the antioxidant and oxygen generation ability of glucose and MnO2, as well as the precise delivery mechanism of miR-146a, to form a hydrogel that can quickly release GOx and miR-146a in a high sugar environment.
Local blood sugar regulation in a high-sugar environment is achieved, which alleviates the damage of high-sugar to cell function, stabilizes the wound microenvironment, promotes cell metabolism and tissue repair, and avoids the side effects of traditional treatments.
Smart Images

Figure CN119868258A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a method for preparing a glucose-responsive genetic material delivery hydrogel. Background Art
[0002] The treatment of chronic diabetic wounds is one of the major challenges in clinical treatment. The difficulty in healing is mainly due to a series of complex factors such as persistent inflammatory response caused by chronic high-sugar environment, increased reactive oxygen species (ROS) levels, local hypoxia, and imbalance of macrophage polarization. These pathological characteristics lead to local angiogenesis obstruction, impaired fibroblast function, and insufficient deposition of extracellular matrix (ECM), which seriously delays or even hinders the normal healing of wounds. According to statistics, the amputation rate of patients with diabetic wounds is much higher than that of non-diabetic patients, and the life expectancy of these patients is significantly shortened.
[0003] According to existing literature, miR-146a, as an important regulatory factor, is generally downregulated in diabetic wounds, while it remains stably expressed in normal wounds. Studies have shown that excessive delivery of miRNA may cause nonspecific gene interference and even lead to immune and metabolic abnormalities.
[0004] In order to solve the problem of diabetic wound healing, many treatment strategies have been proposed, such as the topical use of anti-inflammatory drugs, antioxidants, topical dressings or functional hydrogels. However, these traditional treatments have significant shortcomings. For example, the local anti-inflammatory effect is limited: in a high-sugar environment, it is difficult for macrophages to effectively transform from M1 polarization to M2 polarization, and inflammation persists for a long time. In addition, the antioxidant efficiency is insufficient: existing antioxidants cannot quickly remove high concentrations of ROS in the wound, and the continuous accumulation of ROS will further damage the tissue. The most critical thing is the lack of intelligent responsiveness: most materials are difficult to respond specifically to the wound microenvironment (such as high concentrations of glucose), resulting in low drug release efficiency. The borate bond is a dynamic covalent bond with dynamic reversibility. It uses its sensitivity to glucose to form a glucose-responsive genetic material delivery hydrogel for the treatment of diabetic wounds, which has positive significance. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides a method for preparing a glucose-responsive genetic material delivery hydrogel, which utilizes the sensitivity of boronate bonds to glucose, loads GOx, MnO2, and miR-146a in the hydrogel, combines GOx catalytic degradation of glucose, the antioxidant and oxygen generation capabilities of MnO2 nanoparticles, and the precise delivery mechanism of miR-146a, to form a glucose-responsive genetic material delivery hydrogel. The present invention achieves morphological regulation of the hydrogel in a high-sugar environment by introducing boronate bonds in the hydrogel, and achieves the purpose of rapid release of GOx in high sugar.
[0006] The present invention solves the technical problem by adopting the following technical solutions:
[0007] The object of the present invention is to provide a method for preparing a glucose-responsive genetic material delivery hydrogel, comprising the following steps:
[0008] 1) Preparation of hollow nanoparticles: Hollow MnO2 nanoparticles were synthesized using SiO2 templates by chemical etching;
[0009] 2) Preparation of a microRNA-loaded complex: using a cationic polymer to modify the hollow MnO2 nanoparticles obtained in step 1), and then adding microRNA to obtain a microRNA-loaded complex;
[0010] 3) Hydrogel and nanoparticle complex: The microRNA-loaded complex obtained in step 2), the hydrogel, and GOx are mixed to obtain a glucose-responsive genetic material delivery hydrogel.
[0011] Furthermore, the preparation method of the hollow MnO2 nanoparticles is: adding KMnO4 to the SiO2 aqueous dispersion, after ultrasonication, centrifugation and water washing, the obtained precipitate is dispersed with a Na2CO3 solution to obtain hollow MnO2 nanoparticles.
[0012] Furthermore, the concentration of the SiO2 aqueous dispersion is 35-70 mg / ml.
[0013] Furthermore, the SiO2 is nano-SiO2 with a particle size of 100 to 200 nm.
[0014] Furthermore, the molar ratio of SiO2 to KMnO4 is 1:3-5.
[0015] Furthermore, the cationic polymer is PEI.
[0016] Furthermore, the preparation method of the microRNA-loaded complex is: adding hollow MnO2 nanoparticles to PEI solution and magnetically stirring for 1.5 to 3 hours to make them evenly dispersed, and then centrifuging and washing with water twice to obtain HMnO2@PEI; dissolving microRNA with PBS, and then adding the solution to HMnO2@PEI and stirring, and then centrifuging and washing with water to obtain the microRNA-loaded complex.
[0017] Furthermore, the mass ratio of the hollow MnO2 nanoparticles to microRNA is 5-20 mg: 0.5-2 OD.
[0018] Furthermore, the hydrogel is a GC-PBA+PAA-DA hydrogel, and the preparation method of the GC-PBA+PAA-DA hydrogel is as follows: hydroxyethyl deacetylated chitosan and 3-carboxyphenylboric acid form GC-PBA, sodium polyacrylate and dopamine hydrochloride form PAA-DA, and the obtained GC-PBA and PAA-DA are mixed with PBS.
[0019] Furthermore, the GC-PBA is prepared by dissolving hydroxyethyl chitosan (GC) and 3-carboxyphenylboronic acid (PBA) in a PBS solution, adding EDC and NHS, stirring for 24 hours, dialyzing, and freeze-drying.
[0020] Furthermore, the PAA-DA is prepared by adding sodium polyacrylate (PAA) into a PBS solution, then adding EDC and NHS, stirring evenly, then adding dopamine hydrochloride (DA), continuing the reaction for 24 hours, dialyzing, and freeze-drying.
[0021] Furthermore, the molar ratio of GC to PBA is 1:1, and the molar ratio of PAA to DA is 1:1.
[0022] Furthermore, in the GC-PBA+PAA-DA hydrogel in step 4), the mass ratio of GC-PBA to PAA-DA is 1:1, and before mixing, 2% GC-PBA and 2% PAA-DA are dissolved in PBS and then mixed.
[0023] Furthermore, the mass ratio of the GOx to the microRNA-loaded complex is 2:5.
[0024] Furthermore, a method for preparing a glucose-responsive genetic material delivery hydrogel comprises the following steps:
[0025] 1) Preparation of hollow nanoparticles: KMnO4 was added to SiO2 aqueous dispersion, and after ultrasonication, centrifugation and water washing, the obtained precipitate was dispersed with Na2CO3 solution to obtain hollow MnO2 nanoparticles;
[0026] 2) Preparation of a microRNA-loaded complex: adding the hollow MnO2 nanoparticles obtained in step 1) to a PEI solution and magnetically stirring for 1.5 to 3 hours to make them uniformly dispersed, and washing them with water twice by centrifugation to obtain HMnO2@PEI; dissolving the microRNA with PBS, and then adding the solution to the HMnO2@PEI and stirring, and washing them with water by centrifugation to obtain the microRNA-loaded complex (HMnO2@PEI@microRNA);
[0027] 3) Preparation of hydrogel: Hydroxyethyl chitosan (GC) and 3-carboxyphenylboronic acid (PBA) were dissolved in PBS solution, and then EDC and NHS were added, stirred for 24 hours, dialyzed, and freeze-dried to obtain GC-PBA; sodium polyacrylate (PAA) was added to PBS solution, and then EDC and NHS were added, stirred evenly, and then dopamine hydrochloride (DA) was added, and the reaction was continued for 24 hours, dialyzed, and freeze-dried to obtain PAA-DA; GC-PBA and PAA-DA obtained in a mass ratio of 1:1 were mixed with PBS to prepare GC-PBA+PAA-DA hydrogel;
[0028] 4) Hydrogel and nanoparticle complex: The microRNA-loaded complex obtained in step 2), the GC-PBA+PAA-DA hydrogel obtained in step 3), and GOx are mixed to obtain a glucose-responsive genetic material delivery hydrogel.
[0029] Furthermore, the microRNA is miR-146a.
[0030] Compared with the prior art, the beneficial technical effects of the present invention are:
[0031] The present invention utilizes the sensitivity of boronate bonds to glucose, loads GOx, MnO2, and miR-146a in hydrogels, combines the catalytic degradation of glucose by GOx, the antioxidant and oxygen generation capabilities of MnO2 nanoparticles, and the precise delivery mechanism of miR-146a, and is used for local treatment of diabetic wounds. The present invention achieves morphological regulation of hydrogels in a high-sugar environment by introducing boronate bonds in the hydrogel, and achieves the purpose of rapid release of GOx in high-sugar environments.
[0032] By loading GOx in the hydrogel, local blood sugar regulation in a high-sugar environment is achieved. GOx catalyzes the conversion of glucose into glucuronic acid and hydrogen peroxide, effectively reducing the local blood sugar level on the wound surface, thereby alleviating the continuous damage of high sugar to cell function. Compared with traditional systemic insulin therapy, this strategy shows higher wound targeting and avoids common side effects such as hypoglycemia and insulin resistance.
[0033] The present invention introduces MnO2 nanoparticles, which utilize their excellent antioxidant properties to effectively remove local ROS, reduce oxidative stress, and decompose the hydrogen peroxide produced by GOx to prevent its accumulation in the wound microenvironment, thereby avoiding the possibility that hydrogen peroxide produced during the GOx catalytic process may induce oxidative stress and have a negative impact on wound healing. More importantly, MnO2 can also produce oxygen, alleviate the common local hypoxia problem in diabetic wounds, and provide sufficient oxygen support for the repair of wound tissue. This strategy not only stabilizes the wound microenvironment, but also creates favorable conditions for cell metabolism and tissue repair.
[0034] The present invention ensures that miR-146a is released only in a wound environment with a high blood sugar level by constructing a complex of hollow MnO2 nanoparticles and PEI. MnO2-grafted PEI can effectively adsorb negatively charged miR-146a as a positive charge carrier. When the sugar concentration in the local environment of the wound increases, the hydrogen peroxide generated by the GOx catalytic reaction will cause MnO2 to undergo conformational changes, thereby promoting the release of miR-146a. This response mechanism ensures that more miR-146a is released in diabetic wounds with higher blood sugar levels, and avoids the release of too much miR-146a in diabetic wounds with relatively low blood sugar levels, excessively suppressing necessary immune responses, and causing delayed wound debridement and repair or overexpression of miR-146a triggering potential autoimmunity or metabolic abnormalities.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The particle size analysis diagram of HMnO2, HMnO2@PEI and HMnO2@PEI@microRNA obtained in Example 1 of the present invention.
[0037] Figure 2 This is a transmission electron microscope scanning image of HMnO2@PEI@microRNA obtained in Example 1 of the present invention.
[0038] Figure 3 This is the EDS elemental analysis diagram of HMnO2@PEI@microRNA obtained in Example 1 of the present invention.
[0039] Figure 4 This is a Zeiss scanning electron microscope morphology image in Experimental Example 2 of the present invention (the left side is the morphology image when no glucose is added, and the right side is the morphology image after adding glucose).
[0040] Figure 5 This is a frequency scanning diagram in Experimental Example 2 of the present invention.
[0041] Figure 6 This is the strain scanning diagram in Experimental Example 2 of the present invention.
[0042] Figure 7 This is a graph showing the relationship between viscosity and shear rate in Experimental Example 2 of the present invention.
[0043] Figure 8 This is a graph showing the relationship between viscosity and shear stress in Experimental Example 2 of the present invention.
[0044] Fig. 9 This is a diagram of the microRNA release experiment in Experimental Example 3 of the present invention.
[0045] Fig.10 This is a diagram of the dissolved oxygen experiment in Experimental Example 4 of the present invention. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection that the present invention is intended to protect.
[0047] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0048] Example 1
[0049] A method for preparing a glucose-responsive genetic material delivery hydrogel comprises the following steps:
[0050] 1) Preparation of hollow nanoparticles: Prepare 50 mg / ml SiO2 aqueous dispersion, add 150 mg KMnO4 to the SiO2 aqueous dispersion, ultrasonicate for 6 h, centrifuge, wash with water 3 times, disperse the obtained precipitate with 20 ml 2 mol / L Na2CO3 solution, stir overnight at 60°C, centrifuge, and wash with water 3 times to obtain hollow MnO2 nanoparticles (HMnO2);
[0051] 2) Preparation of microRNA-loaded complex: 10 mg of HMnO2 nanoparticles obtained in step 1) were added to 4 ml of 0.5 mg / ml PEI solution and magnetically stirred for 2 h to make them dispersed evenly, and then centrifuged and washed twice to obtain HMnO2@PEI; 1 OD of microRNA was dissolved in 1 ml of PBS, and then the solution was added to HMnO2@PEI and stirred for 2 h, and then centrifuged and washed to obtain a microRNA-loaded complex (HMnO2@PEI@microRNA);
[0052] 3) Preparation of hydrogel: 1 g of hydroxyethyl chitosan (GC) and 0.85 g of 3-carboxyphenylboronic acid (PBA) were dissolved in 400 ml of PBS solution at pH = 5.5, and then 30 mg of EDC and 50 mg of NHS were added, stirred for 24 h, dialyzed, and freeze-dried to obtain GC-PBA; 1 g of sodium polyacrylate (PAA) was added to 50 ml of PBS solution at pH = 5.5, and then 10 mg of EDC and 8 mg of NHS were added, stirred evenly, and then 50 mg of dopamine hydrochloride (DA) was added, and the reaction was continued for 24 h, dialyzed, and freeze-dried to obtain PAA-DA; GC-PBA and PAA-DA obtained in a mass ratio of 1:1 were mixed with 0.1 M PBS to prepare a 2% GC-PBA + 2% PAA-DA hydrogel;
[0053] 4) Hydrogel and nanoparticle composite: 5 mg HMnO2@PEI@microRNA obtained in step 2), 2% GC-PBA+2% PAA-DA hydrogel obtained in step 3), and 2 mg GOx were mixed to obtain a glucose-responsive genetic material delivery hydrogel.
[0054] Example 2
[0055] A method for preparing a glucose-responsive genetic material delivery hydrogel comprises the following steps:
[0056] 1) Preparation of hollow nanoparticles: prepare 60 mg / ml SiO2 aqueous dispersion, add 200 mg KMnO4 to the SiO2 aqueous dispersion, ultrasonicate for 6 h, centrifuge, wash with water 3 times, disperse the obtained precipitate with 20 ml 2 mol / L Na2CO3 solution, stir overnight at 60°C, centrifuge, wash with water 3 times to obtain hollow MnO2 nanoparticles (HMnO2);
[0057] 2) Preparation of microRNA-loaded complex: 10 mg of HMnO2 nanoparticles obtained in step 1) were added to 4 ml of 0.5 mg / ml PEI solution and magnetically stirred for 3 h to make them dispersed evenly, and then centrifuged and washed twice to obtain HMnO2@PEI; 2 OD of microRNA was dissolved in 2 ml of PBS, and then the solution was added to HMnO2@PEI and stirred for 2 h, and then centrifuged and washed to obtain a microRNA-loaded complex (HMnO2@PEI@microRNA);
[0058] 3) Preparation of hydrogel: 1 g of hydroxyethyl chitosan (GC) and 0.85 g of 3-carboxyphenylboronic acid (PBA) were dissolved in 400 ml of PBS solution at pH = 5.5, and then 30 mg of EDC and 50 mg of NHS were added, stirred for 24 h, dialyzed, and freeze-dried to obtain GC-PBA; 1 g of sodium polyacrylate (PAA) was added to 50 ml of PBS solution at pH = 5.5, and then 10 mg of EDC and 8 mg of NHS were added, stirred evenly, and then 50 mg of dopamine hydrochloride (DA) was added, and the reaction was continued for 24 h, dialyzed, and freeze-dried to obtain PAA-DA; GC-PBA and PAA-DA obtained in a mass ratio of 1:1 were mixed with 0.1 M PBS to prepare a 2% GC-PBA + 2% PAA-DA hydrogel;
[0059] 4) Hydrogel and nanoparticle composite: 5 mg HMnO2@PEI@microRNA obtained in step 2), 2% GC-PBA+2% PAA-DA obtained in step 3), and 2 mg GOx were mixed to obtain a glucose-responsive genetic material delivery hydrogel.
[0060] Experimental Example 1
[0061] The particle size of HMnO2, HMnO2@PEI and HMnO2@PEI@microRNA obtained in Example 1 was analyzed by NanoBrook Omni (Brookhaven Instruments, UK) particle size analyzer, see Appendix Figure 1 . It can be seen that the particle size of the unmodified HMnO2 particles is 189.57±5.32nm and the PDI is 0.18. After modification, the particle size of HMnO2@PEI and HMnO2@PEI@microRNA gradually increases to 220.81±5.25nm, and the PDI of the modified HMnO2@PEI@microRNA drops to 0.09. It can be seen that the stability and controllability of the particles are improved through the modification process. The Zeta potential increased significantly from -19.83±1.53mV to -4.69±1.03mV (PEI modification), and dropped to -10.54±1.31mV after the introduction of microRNA, indicating that the cationic PEI was successfully coated to neutralize the surface negative charge, while the microRNA binding re-increased the negative charge. The coordinated changes in particle size and potential not only verify the successful modification, but also reflect the precise regulation of the particle surface environment.
[0062] The HMnO2@PEI@microRN obtained in Example 1 was scanned using a transmission electron microscope. During the operation, ethanol was used for dispersion and then dropped onto the copper mesh carbon film. After drying, the morphology of the nanoparticles was observed using a transmission electron microscope. Figure 2 .
[0063] The HMnO2@PEI@microRN obtained in Example 1 was detected using an elemental analysis device in EDS mode (JEM-F200, Japan). Figure 3 It can be seen that all elements are almost distributed around the shell, and most of the PEI molecules cover the surface of the nanoparticles, forming a complete protective film.
[0064] Example 2 Mechanical properties test
[0065] In this experimental example, a sample obtained by immersing the glucose-responsive genetic material delivery hydrogel obtained in Example 1 in a 4 mg / L glucose solution for 5 minutes was used as a comparative example and compared with the glucose-responsive genetic material delivery hydrogel obtained in Example 1.
[0066] Morphology detection comparison:
[0067] The morphology of the glucose-responsive genetic material delivery hydrogel obtained in Example 1 was observed using a Zeiss scanning electron microscope and compared with that of the comparative example, and the acceleration voltage used was 3 kV. Figure 4 . It can be seen that when glucose is not added, the pore wall is relatively uniform, and there are more flexible segments that can maintain a larger pore size, indicating that the network cross-linking points are relatively stable and expanded at this time, and the hydrogel can maintain a larger porosity in the swollen state. After the addition of glucose, the densification of the gel structure indicates that the internal cross-linking points have been readjusted, causing the original large pores to collapse or shrink, forming a denser and potentially more fragile network. This is due to the specific interaction between glucose and the gel segments, which causes the swelling equilibrium conditions to change, and the system tends to shrink or restructure. This reorganization weakens the macro-elasticity, making the gel more easily destroyed under external forces and enhancing fluidity.
[0068] Mechanical properties comparison:
[0069] Rheological analysis was performed using a dynamic shear rheometer (DSR, HR-10) (model: TAInstrument):
[0070] Temperature scanning: 18-45°C; Heating rate: 0.5°C / min; Strain: 1%; Frequency: 1Hz; Frequency scanning: Temperature: 37°C; Frequency range: 0.1-100rad / s; Strain: 1%; Strain scanning: Temperature: 37°C; Frequency: 1Hz; Strain range: 0.01%-1000%; Change of viscosity with shear rate: Temperature: 37°C; Shear rate: 0.01-1001 / s and 100-0.011 / s; Change of viscosity with shear stress: Temperature: 37°C; Shear stress: 0.1-0.5kPa. XPS: ESCALAB 250Xi (Thermo, USA).
[0071] The dynamic shear rheometer was used to perform mechanical property tests such as frequency scanning, strain scanning, and the relationship between viscosity and shear stress.
[0072] See attached Figure 5 , which is a frequency scanning test chart. It can be seen that in the state without adding glucose (blue curve), the storage modulus (G') is usually higher and the loss modulus (G") is lower, especially in the low-frequency region. This means that the gel has higher elasticity and a more stable cross-linked network structure. This structure can still maintain strong rigidity and elastic characteristics at lower oscillation frequencies. After adding glucose (black curve), G' decreased significantly, while G" increased relatively. This shows that the gel network becomes looser due to the influence of glucose, and the internal cross-linking points are reduced or weakened, resulting in a decrease in overall elasticity and an increase in viscous components. At low frequencies, this change is particularly obvious: the network is no longer as stable as when no sugar is added, and the elasticity is significantly reduced. This shows that glucose interacts with specific functional groups in the gel, thereby destroying or loosening the original network structure. In short, the addition of glucose causes the hydrogel to change from a more solid elastic behavior to a more fluid and less elastic behavior.
[0073] See attached Figure 6 , which is a strain scanning test graph. It can be seen that in the unsugared state (blue curve), G' remains high and almost unchanged in a wide strain range, indicating a wide linear viscoelastic range (LVER). Only when the strain exceeds a certain threshold will G' drop significantly. This shows that the gel network structure without sugar is relatively strong and has strong deformation resistance. The hydrogel after sugar addition (black curve) begins to decrease in G' at lower strains, which is manifested as a narrowing of the linear viscoelastic zone. The network is more easily destroyed or loosened under smaller deformations. This means that the gel's resistance to external forces is reduced, and the internal structure is more susceptible to disintegration due to small strain disturbances. In short, the addition of glucose makes the gel network "fragile" and loses its elastic network structure earlier during the strain increase process.
[0074] See attached Figure 7 , which is a test graph of the relationship between viscosity and shear rate. It can be seen that the unsugared gel (blue curve) has a higher viscosity at a lower shear rate, indicating that its structure is denser and difficult to flow. As the shear rate increases, the system exhibits a typical shear thinning phenomenon (viscosity decreases), but the initial viscosity is higher. After adding glucose (black curve), the initial viscosity is lower than when no sugar is added. As the shear rate increases, the viscosity decreases more rapidly. This means that after the addition of sugar, the network has been weakened, and it is easier to disentangle or collapse under a smaller external shear action, and it exhibits fluidization behavior more quickly. In short, the addition of sugar reduces the internal viscosity of the gel, making it easier to flow, and the shear thinning effect is more significant.
[0075] See attached Figure 8, which is a test graph of the relationship between viscosity and shear stress. It can be seen that in the unsweetened state (red curve), the gel can still maintain a high viscosity under lower shear stress. This means that there is a certain yield stress in the system: only when the applied shear stress exceeds a certain critical value, the viscosity drops significantly and the gel begins to flow. After adding sugar (black curve), the gel already shows a lower viscosity at a lower shear stress, corresponding to a lower yield stress or almost no yield stress characteristics. As the stress increases, the viscosity decreases rapidly, indicating that the network is easily destroyed by external forces and no longer has obvious "gel" characteristics, but is more like a weak fluid. In short, after the addition of sugar, the system is extremely sensitive to shear stress, and even lower external stress can significantly reduce the viscosity and make the gel fluid.
[0076] From the above experimental results, it can be seen that the unsugared hydrogel has a tight cross-linked network and high mechanical strength, has strong resistance to frequency and strain disturbances, and has a certain yield stress to external forces. After adding glucose, the internal structure of the gel is disturbed, the cross-linking points are weakened or rearranged, making the network loose, fragile, and easier to flow. The storage modulus G' is significantly reduced, the loss modulus G" is relatively increased, and the viscoelastic properties are more inclined to viscous fluids. The hydrogel has good glucose responsiveness and successfully regulates the local microenvironment of the wound surface. The linear viscoelastic range is reduced, which corresponds to easier deformation and destruction under small strains. The overall viscosity is reduced, and the tendency of shear thinning and flow after stress is enhanced.
[0077] Experimental Example 3: microRNA release experiment
[0078] A certain mass of the HMnO2@PEI@microRNA-loaded hydrogel of Example 1 was loaded into a dialysis bag, and the two ends of the dialysis bag were tied and immersed in 100 ml of PBS buffer containing 1 mg / L and 4 mg / L glucose respectively. The container containing all the dissolution medium was placed on a magnetic stirrer and stirred at a speed of 100 r / min at a constant temperature of 37°C. According to the set time node, 1 mL of dissolution medium was taken out each time and then 1 mL of fresh medium was added, and the miRNA content was quantitatively detected using RiboGreen RNA detection reagent (Maokang Biotechnology Co., Ltd., Shanghai).
[0079] See attached Fig. 9Under the condition of low glucose concentration (1 mg / ml), the miRNA release rate is relatively slow, the initial release is low, and the release rate gradually increases with time, but the overall release rate and the final release amount are significantly lower than those under high glucose conditions. Under the condition of high glucose concentration (4 mg / ml), the miRNA release is significantly accelerated, the initial release increases sharply, and a higher release rate is reached in a short time. The final cumulative release ratio is significantly higher than that under low glucose conditions. This means that the network structure, porosity or cross-linking density of the hydrogel is very sensitive to glucose stimulation. When the external glucose concentration rises, the structure loosens, the swelling changes or the dynamic bonding points change inside the hydrogel, thereby promoting the loaded miRNA molecules to diffuse out faster and more efficiently. When the glucose concentration in the external solution increases, phenylboronic acid forms a reversible complex with glucose, which changes the cross-linking state of the entire gel. At the same time, if there are enzymes similar to glucose oxidase in the hydrogel, they will catalyze the glucose conversion process, change the local pH value or ionic strength, and induce the gel to swell or shrink. These structural changes will change the porosity and diffusion path, thereby accelerating the release of miRNA.
[0080] Experimental Example 4 Dissolved oxygen experiment
[0081] A certain amount of HMnO2@PEI@microRNA-loaded hydrogel was placed in 50 ml of glucose solution containing 1 mg / L and 4 mg / L concentrations, respectively. The probe was fixed at a certain position, and a JPSJ605F dissolved oxygen analyzer (Yitian Scientific Instrument Co., Ltd., Shanghai) was used to detect the dissolved oxygen content in the solution at different time points.
[0082] See attached Fig.10 , under 1mg / L glucose conditions, the dissolved oxygen level starts from a low value and gradually increases over time, but the growth rate is relatively slow, and finally reaches a higher but limited equilibrium value. Under 4mg / L glucose conditions, the increase in dissolved oxygen is more rapid and obvious. At the same time point, the total amount of dissolved oxygen under high glucose conditions is much higher than that under low glucose conditions. Dissolved oxygen rises rapidly and continuously until it reaches a higher equilibrium value. Glucose oxidase (GOx), when there is enough glucose, oxidizes glucose into glucuronic acid, while consuming oxygen to generate H2O2, which is further decomposed into water and oxygen under the action of manganese dioxide, resulting in an increase in the oxygen concentration in the local solution. When the external glucose concentration is high (4mg / L), the rate of this enzymatic reaction is faster, resulting in more O2 being generated and dissolved in the water phase, so the dissolved oxygen concentration rises rapidly.
[0083] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0084] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing a glucose-responsive genetic material delivery hydrogel, characterized in that: The following steps are involved: 1) Preparation of hollow nanoparticles: Hollow MnO2 nanoparticles were synthesized using SiO2 templates by chemical etching; 2) Preparation of a microRNA-loaded complex: using a cationic polymer to modify the hollow MnO2 nanoparticles obtained in step 1), and then adding microRNA to obtain a microRNA-loaded complex; 3) Hydrogel and nanoparticle complex: The microRNA-loaded complex obtained in step 2), the hydrogel, and GOx are mixed to obtain a glucose-responsive genetic material delivery hydrogel.
2. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 1, characterized in that: The preparation method of the hollow MnO2 nanoparticles is as follows: KMnO4 is added to SiO2 aqueous dispersion, and after ultrasonication, centrifugation and water washing, the obtained precipitate is dispersed with a Na2CO3 solution to obtain the hollow MnO2 nanoparticles.
3. The method for preparing a glucose-responsive genetic material delivery hydrogel as claimed in claim 2, characterized in that: The molar ratio of SiO2 to KMnO4 is 1:3-5.
4. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 1, characterized in that: The cationic polymer is PEI.
5. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 4, characterized in that: The preparation method of the microRNA-loaded complex is as follows: hollow MnO2 nanoparticles are added to a PEI solution and magnetically stirred for 1.5 to 3 hours to make them evenly dispersed, and then centrifuged and washed twice to obtain HMnO2@PEI; microRNA is dissolved in PBS, and then the solution is added to HMnO2@PEI and stirred, and then centrifuged and washed to obtain the microRNA-loaded complex.
6. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 5, characterized in that: The mass ratio of the hollow MnO2 nanoparticles to the microRNA is 5-20 mg: 0.5-2 OD.
7. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 1, characterized in that: The hydrogel is a GC-PBA+PAA-DA hydrogel, and the preparation method of the GC-PBA+PAA-DA hydrogel is as follows: hydroxyethyl deacetylated chitosan and 3-carboxyphenylboric acid form GC-PBA, sodium polyacrylate and dopamine hydrochloride form PAA-DA, and the obtained GC-PBA and PAA-DA are mixed with PBS to obtain the hydrogel.
8. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 7, characterized in that: The GC-PBA is prepared by dissolving hydroxyethyl chitosan (GC) and 3-carboxyphenylboronic acid (PBA) in a PBS solution, adding EDC and NHS, stirring for 24 hours, dialyzing, and freeze-drying.
9. The method for preparing a glucose-responsive genetic material delivery hydrogel according to claim 7, characterized in that: The PAA-DA is prepared by adding sodium polyacrylate (PAA) into a PBS solution, then adding EDC and NHS, stirring evenly, then adding dopamine hydrochloride (DA), continuing the reaction for 24 hours, dialyzing, and freeze-drying.
10. A method for preparing a glucose-responsive genetic material delivery hydrogel according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Preparation of hollow nanoparticles: KMnO4 was added to SiO2 aqueous dispersion, and after ultrasonication, centrifugation and water washing, the obtained precipitate was dispersed with Na2CO3 solution to obtain hollow MnO2 nanoparticles; 2) Preparation of a microRNA-loaded complex: adding the hollow MnO2 nanoparticles obtained in step 1) to a PEI solution and magnetically stirring for 1.5 to 3 hours to make them uniformly dispersed, and washing them with water twice by centrifugation to obtain HMnO2@PEI; dissolving the microRNA with PBS, and then adding the solution to the HMnO2@PEI and stirring, and washing them with water by centrifugation to obtain the microRNA-loaded complex (HMnO2@PEI@microRNA); 3) Preparation of hydrogel: Hydroxyethyl chitosan (GC) and 3-carboxyphenylboronic acid (PBA) were dissolved in PBS solution, EDC and NHS were added, stirred for 24 h, dialyzed and freeze-dried to obtain GC-PBA; Sodium polyacrylate (PAA) was added to PBS solution, and then EDC and NHS were added, stirred evenly, and then dopamine hydrochloride (DA) was added, and the reaction was continued for 24 hours, dialyzed, and freeze-dried to obtain PAA-DA; GC-PBA and PAA-DA obtained in a mass ratio of 1:1 were mixed with PBS to prepare GC-PBA+PAA-DA hydrogel; 4) Hydrogel and nanoparticle complex: The microRNA-loaded complex obtained in step 2), the GC-PBA+PAA-DA hydrogel obtained in step 3), and GOx are mixed to obtain a glucose-responsive genetic material delivery hydrogel.